Electric currents of a substorm current wedge on 24 February 2010. Issue 13 (15th July 2014) - Connors, Martin; McPherron, Robert L.; Anderson, Brian J.; Korth, Haje; Russell, Christopher T.; Chu, Xiangning
Abstract The three‐dimensional "substorm current wedge" (SCW) was postulated by McPherron et al. (1973) to explain substorm magnetic perturbations. The origin and coherence as a physical system of this important paradigm of modern space physics remained unclear, however, with progress hindered by gross undersampling, and uniqueness problems in data inversion. Complementing AMPERE (Active Magnetosphere and Planetary Electrodynamics Response Experiment) space‐derived radial electric currents with ground magnetic data allowing us to determine currents from the ionosphere up, we overcome problems of uniqueness identified by Fukushima (1969, 1994). For a substorm on 24 February 2010, we quantify SCW development consistently from ground and space data. Its westward electrojet carries 0.5 MA in the more poleward part of the auroral oval, in Region 1 (R1) sense spanning midnight. The evening sector electrojet also feeds into its upward current. We thus validate the SCW concept and obtain parameters needed for quantitative study of substorms.